The effect of transfer pricing, earnings management, and company size on tax avoidance: Managerial ownership analysis - Paulus, Hendro; Tarmidi, Deden; Daito, Apollo (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study investigates the effect of transfer pricing, earnings management, and firm size on tax avoidance, with managerial ownership as a distinguishing factor. Using a sample of 43 manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023, the study employs panel data regression with the Common Effect Model. The results show a significant negative effect of transfer pricing on tax avoidance in companies without managerial ownership, indicating its use as an active tax avoidance strategy. Conversely, this effect is insignificant in firms with managerial ownership, suggesting greater caution due to reputational risks. Earnings management significantly affects tax avoidance in firms with managerial ownership, highlighting the dual role of managers as decision-makers and shareholders. Firm size, however, does not significantly influence tax avoidance across both types of ownership. These findings emphasize the moderating role of managerial ownership and support agency theory by illustrating how ownership structure shapes strategic financial behavior. This study contributes to the literature by offering a more nuanced understanding of tax avoidance practices in Indonesia’s manufacturing sector.